1998
DOI: 10.2307/2585933
|View full text |Cite
|
Sign up to set email alerts
|

Minority Representation in Multimember Districts

Abstract: Given the recent court rulings against racial gerrymandering, the effect of multimember district elections on minority representation is an important issue. We present a model of voting in double-member district elections with two majority candidates and one minority candidate and consider the voting equilibria under straight and cumulative voting. In straight voting, while an equilibrium always exists in which the two majority candidates are expected to win the two seats, minority candidates may be elected. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
87
1
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 97 publications
(91 citation statements)
references
References 20 publications
2
87
1
1
Order By: Relevance
“…Later, we examine what types of equilibria exist for each set of parameter values. Following Cox [10] and Gerber, Morton and Rietz [13], we assume additivity of utility. For example, if candidates 1 and 2 win seats, type-c voters receive a utility of c 1 + c 2 .…”
Section: Preferencesmentioning
confidence: 99%
See 4 more Smart Citations
“…Later, we examine what types of equilibria exist for each set of parameter values. Following Cox [10] and Gerber, Morton and Rietz [13], we assume additivity of utility. For example, if candidates 1 and 2 win seats, type-c voters receive a utility of c 1 + c 2 .…”
Section: Preferencesmentioning
confidence: 99%
“…Their results are in contrast to the view of Duverger, who suggested that strategic voting would not appear under PR. Second, the model-building strategy proposed herein is based on the research of Myerson and Weber [7] and Gerber, Morton and Rietz [13]. Myerson and Weber [7] introduced voter perception of the probability of close races between each pair of candidates and required consistency between the perception and the electoral outcome.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations